Evaluation of economic sustainability ecological production vegetables on family farms in Serbia - Jonel Subić; Svetlana Roljević Nikolić; Zoran Simonović (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The tendency of conventional agriculture to achieve high yields has imposed a need for specialization of production and intensive application of mechanization, irrigation, pesticides, mineral fertilizers and new plant varieties. In this way, on the one hand, the profit of farmers is significantly increasing, while on the other hand serious harmful consequences are caused to the environment. Therefore, in recent decades developed different models of sustainable agriculture, which are environmentally friendly and socially just, but they are often criticized that was not economically payable as conventional production method. The research was conducted in the period from January to October 2018, following the production of tomatoes, cv. Big beef, in a greenhouse, on two family farms. The paper presents a gross margin of conventional and ecological production of tomatoes, then gives an overview of the structure of the variable costs and the critical value of production, as well as the way of changing the gross margin due to the growth of variable costs and / or decline in yields and product prices. The results of the research showed that the total value of environmentally friendly production of tomatoes in the greenhouse increased by 29.6% compared to conventional production of the same crop. However, costs of laboratory analyzes of the quality of soil, irrigation water and fruits, as well as labor costs significantly increase the amount of variable costs in ecological production, which results in lower gross margin for 13.5% compared to conventional cultivation practices. It was also found that the decline in production value has a greater impact on the gross margin than the increase in the cost of the production both in environmentally friendly and conventional agriculture.
Keywords: Q12; Q15; Q16; 330; ecological production; economic sustainability; calculation of production costs; gross margin